Robot-assisted kidney transplantation. First experience - S. V. Shchekaturov; I. V. Semeniakin; A. K. Zokoev; T. B. Makhmudov; R. R. Poghosyan (Вестник трансплантологии и искусственных органов)
Kidney transplantation is the preferred renal replacement therapy for patients with end-stage renal disease. Traditional surgical approaches consisting of vascular and urinary outflow reconstruction during kidney transplant have been sufficiently studied and standardized. However, surgical techniques are still evolving. The objective of this clinical report is to focus the attention of kidney transplant surgeons and specialists on the currently trending robot-assisted kidney transplantation (RAKT) as a minimally invasive procedure for surgical treatment of patients with end-stage renal disease. In our first experience, good primary graft function was achieved. This shows that RAKT is a surgical option. With considerable number of surgeries and experience, RAKT outcomes would be improved significantly.